2019
DOI: 10.1021/acs.chemmater.9b01785
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Atomic Structure and Oxidation States of Dopants in Charge-Ordered Nanoparticles for Migration-Promoted Oxygen-Exchange Capacity

Abstract: Doping of nanomaterials has become a versatile approach to tailoring their physical and chemical properties, leading to the emerging fields of solotronics and quantumcontrolled catalysis. These extraordinary functionalities critically depend on the atomic arrangements and dynamic behaviors of dopants, which are however challenging to probe due to the ultrasmall volume of hosting nanomaterials and the even smaller scale of doping-induced structure variations. Here, we reveal the characteristic configurations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Here, we combine the electronic structure information obtained from EELS with atomic-level scanning transmission electron microscopy (STEM) imaging collected in situ during thermal reduction to characterize the electronic and structural transformations occurring in BCM, thus revealing important mechanistic insights into the redox behavior of STCH materials. 21,22,29,30 In the current work, we probe at the atomic level how the formation of new phases and crystalline defects accommodate oxygen vacancies during the thermal reduction of Ba-Ce 0.25 Mn 0.75 O 3 . The unique bonding environment in 12R-BCM contains chains of three MnO 6 face-sharing octahedra (FSO) separated by rows of Ce atoms in a perfect crystal.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we combine the electronic structure information obtained from EELS with atomic-level scanning transmission electron microscopy (STEM) imaging collected in situ during thermal reduction to characterize the electronic and structural transformations occurring in BCM, thus revealing important mechanistic insights into the redox behavior of STCH materials. 21,22,29,30 In the current work, we probe at the atomic level how the formation of new phases and crystalline defects accommodate oxygen vacancies during the thermal reduction of Ba-Ce 0.25 Mn 0.75 O 3 . The unique bonding environment in 12R-BCM contains chains of three MnO 6 face-sharing octahedra (FSO) separated by rows of Ce atoms in a perfect crystal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While defect formation has been reported in other perovskite systems upon thermal reduction, , the atomic mechanisms of these structural transformations cannot be easily investigated using traditional bulk analysis techniques, such as XRD or X-ray absorption spectroscopy. Electron spectral microscopy is a valuable technique that provides atomic-level insight into the crystal structure and electronic structure in local regions of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Later in another work by Zhu et al, the high mobility of Ce with the formation of CeO 2 nanoclusters has been identified by the atomic‐resolution electron energy‐loss spectroscopic mapping. [ 140 ] The oxygen‐exchange mechanism further supports the ability of mobile Ce 4+ to carry oxygen or create oxygen vacancies to enhance oxygen transport. These preliminary works have supplied insightful information on the intrinsic activity of CeO 2 .…”
Section: Theoretical Explorations Of Ceo2‐based Catalystsmentioning
confidence: 88%
“…Additionally, advanced analytical microscopy techniques coupled to the microscope will shed light on optical and optoelectronic properties. 418 Advances in electron energy loss spectroscopy (EELS, used in STEM), 419 in particular, could give further insight on the connection between composition (e.g., doping levels, oxidation states) 420 and electronic structure (bandgap, plasmon frequencies, etc. [421][422][423] ), temporal transformation of chemical properties 424 and atomic-resolution of interfaces of complex nanostructures.…”
Section: Perspectivementioning
confidence: 99%